Tacrolimus versus Cyclosporine- Comparative Evaluation as First line drug in Vernal keratoconjuctivitis - Kumari, Rashmi; Saha, Bhawesh Chandra; Sinha, Bibhuti Prasanna; Mohan, Nilesh (Nepalese Journal of Ophthalmology, 2018)
Introduction: The aim of the study was to evaluate and compare the efficacy, side effects and recurrence rate of vernal kerato conjunctivitis (VKC) with 0.03% tacrolimus and 0.05% cyclosporin. Material and method: A prospective randomised double blinded comparative study was conducted at a tertiary eye center. 46 Patients of VKC between March 2015- August 2015 were randomly divided into two groups and treated for 6weeks with either Tacrolimus(0.03%) eye ointment BD or Cyclosporine (0.05%) eyedrops QID.The main outcome measures were scoring and comparison of Total subjective symptom scores (TSSS) and Total objective ocular sign scores (TOSS) within and between the Groups at each follow up.Thirty two patients, sixteen from each group, with comparable baseline characters were analysed. Results: With treatment both TSSS and TOSS decreased consistently in both groups without any adverse effects but an increase in scores was noticed within two weeks after drug withdrawal. Conclusion: Both drugs are equally effective and safe in VKC but with short lasting effect.